2019
DOI: 10.1590/0004-282x20190002
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome: are stroke neurologists at a higher risk?

Abstract: Background: Burnout syndrome is a work-related psychological response, characterized by emotional exhaustion, depersonalization and low professional accomplishment. Objective: The study aimed to evaluate the prevalence of burnout syndrome in neurologists in the State of Paraná, Brazil, dividing them into stroke neurologists and non-stroke neurologists. Methods: We performed a crosssectional observational study, with a quantitative approach, based on the online Maslach Burnout Inventory - Human Services Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…Besides that, EPs often take on heavy workloads, deal with the unpredictable circumstances, and are expected to make decisions under pressure. These factors contribute to physician burnout and can reduce their career lengths 12,13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, EPs often take on heavy workloads, deal with the unpredictable circumstances, and are expected to make decisions under pressure. These factors contribute to physician burnout and can reduce their career lengths 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…These factors contribute to physician burnout and can reduce their career lengths. 12,13 While manual ASPECTS scoring has a modest interobserver agreement, the use of E-ASPECTS software has increased interrater agreement and the accuracy of infarct extent evaluation in groups of neuroradiologists and neurologists. 14,15 Neuhaus and colleagues studied 16 physicians, including vascular and general neurologists, neuroradiologists, and junior neuroradiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Os sintomas do estresse comportam três fases: a primeira se refere à reação de defesa ou de alarme e que tem como sintomas a taquicardia, a palidez, a fadiga, a insônia e falta de apetite; a segunda fase é denominada como de resistência ou adaptativa, a qual o indivíduo evidencia sintomatologia relacionada ao isolamento social, à incapacidade de desligar-se do trabalho, à irritabilidade excessiva e à diminuição da libido; a terceira fase, por sua vez, se apresenta como estágio de exaustão ou esgotamento. Nesta fase, o indivíduo apresenta problemas como hipertensão arterial, depressão, ansiedade, problemas sexuais e dermatológicos, como psoríase, vitiligo, urticárias e alergia, além do infarto e até da morte súbita 24 .…”
Section: Discussionunclassified
“…A recent Brazilian study found that 44.6% of the neurologists fulfill the criteria for severe burnout syndrome, and over 50% were stroke neurologists. 7 The reasons are not well elucidated but can probably be traced to peculiarities of the subspecialty.…”
Section: Stroke Neurology In Focusmentioning
confidence: 99%